e*-Essential Small Submodules and e*-Hollow Modules (European Journal of Pure and Applied Mathematics, 2022)
The purpose of this paper is to introduce new concepts in a module Â over a ring , the first one is called e*- small essential submodule, which is a generalization of the small submodule, the second concept is calledÂ  e*-radical submodule which is a generalization of the radical submodule and the last concept is called e* - hollow module which is a generalization of the hollow module. We will prove some properties of all these concepts.